O uso do sistema operacional LINUX educacional como ferramenta pedagógica na escola José Monteiro Maia do município de Castanhal-PA - SHIMODA, Kayton dos Santos (2023)
The operating systems available in the market are diversified in interface features, available tools and, consequently, also diverse prices. Among them there are free software systems that are free and can be used to the user's liking. The Brazilian government adopts, in its projects of incentive to technological education, the operating system Linux Educacional, a Linux distribution. However, it undergoes a process of disuse when arriving in laboratories due to the lack of training of education professionals regarding this system and the pre-established habit of using proprietary systems. This work consists of a joint research that aims to validate this sad reality through applied research, using a questionnaire and bibliographic studies about the use of the system by these professionals. Given this, the lack of knowledge of the subjects with the system in question is perceptible and the governmental attempts to train these professionals is ineffective. Therefore, it is necessary to implement strategies that can reverse this process.